A Review on Less Tool Wear Rate and Improving Surface Quality of Conductive Ceramic Composites by Spark EDM. (2018) - Selvarajan, L.; M.Manohar,; Amos Robert Jayachandran, J.; Mouri, P; Selvakumar, P.
Abstract: Electrical discharge machining is a process for shaping hard metals and forming deep complex shaped holes by spark erosion in all kinds of electro-conductive materials. A study was carried out on the influence of the parameters such peak current, voltage, pulse on time and pulse off time, electrode diameter, emulsion concentration, electrode vibration. EDM researchers are reported for improving the machining characteristics have been categorized as process parameters optimization, multi spark technique, powder mixed EDM. In this paper authors have reviewed the research work carried out in the development of EDM within the past decades for the improvement of machining characteristics such as Surface Roughness and Tool Wear Ratio. The final part of the paper discusses these developments and outlines the trends for future research work.